2011
DOI: 10.1002/nur.20446
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the multidimensional health locus of control scales for labor and delivery

Abstract: No current instrument assesses women's health locus of control beliefs in relation to childbirth. Form C of the Multidimensional Health Locus of Control Scales was used to develop items for a new instrument specific to labor and delivery (MHLC-LD). Psychometric analyses conducted with two independent samples of pregnant women supported a three-factor model of the new instrument, consisting of Internal, Powerful Others, and Chance subscales. Results revealed modest coefficient alphas (>.70) for the subscales an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Another possibility is that the unsatisfactory reliability and ambiguous factor structure found in China should not be traced back to cultural differences but to target populations. Namely, both previously mentioned Chinese studies examined healthy pregnant women, which is a condition quite different from chronic illnesses such as cancer or diabetes usually studied when employing Form C of the MHLC Scales [43].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the unsatisfactory reliability and ambiguous factor structure found in China should not be traced back to cultural differences but to target populations. Namely, both previously mentioned Chinese studies examined healthy pregnant women, which is a condition quite different from chronic illnesses such as cancer or diabetes usually studied when employing Form C of the MHLC Scales [43].…”
Section: Discussionmentioning
confidence: 99%
“…PCON may be more appropriate to assess perceptions of control over management of birth complications (e.g. preeclampsia, fetal distress) or planned cesarean sections, but the birth itself is not conceptualized as an illness [38].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous research, we demonstrated that the desire for control is only moderately correlated with Internal HLC (Auerbach & Pegg, ; Wallston et al, ). Moreover, desire for control in this study was a stronger predictor (with larger effect sizes) of childbirth choices regarding choice of care provider and doula support compared to HLC (see Stevens et al, ), suggesting that desire for control may play a more direct role in influencing women's health behaviors related to birth. It is worth noting that we observed a rather robust inverse correlation between desire for control and powerful others HLC, ( r = − 0.61; p < 0.001), suggesting that lower desire for personal control of the birth environment is strongly associated with the belief that medical providers are in control of birth outcomes.…”
Section: Discussionmentioning
confidence: 56%
“…Sample 2 participants were recruited from the same antenatal clinic as Sample 1 as well as childbirth classes and Babycenter.com. We used a purposive sampling approach recruiting via both clinic‐based and online sources to obtain responses from a more diverse sample of pregnant women reporting a range of perinatal care choices (see Stevens et al, ). Inclusion criteria for both samples were that the participant should be at least 18 years of age, currently pregnant, and able to read English.…”
Section: Methodsmentioning
confidence: 99%